Educating Students' Spiritual Intelligence: What is the Role of Islamic Education Teachers? - Wulandari, Viona Dwi; Asril, Zainal; Mutathahirin, Mutathahirin; Susanti, Weti; Fitri, Rika; Aulia, Muhammad Zikhra (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2024)
Spiritual intelligence is an important element in the formation of students' character and has a significant impact on their moral development and attitudes in everyday life. This study aims to describe and analyze concrete efforts made by teachers in improving students' spiritual intelligence, as well as understanding the impact of these activities on students' behavior and attitudes. This study uses a qualitative descriptive method, with data collection through interview techniques, observation, and documentation. The main data source comes from interactions with Islamic Religious Education teachers and grade X students at a high school in Indonesia. Data processing is carried out through reductive analysis, data presentation, and concluding so that it can provide a clear picture of the teacher's efforts. The results of the analysis show that the teacher's efforts include implementing religious programs such as: i) congregational dzuhur prayer, ii) cultum, and iii) tahfizul Qur'an, as well as strengthening religious education materials on spiritual values ​​such as patience, humility, and faith. In addition, teachers also control student behavior to ensure they stay away from negative traits. The results of this study are expected to contribute to efforts to improve the quality of religious education in Indonesia.